IMPLEMENTASI PEMODELAN MATEMATIKA MENGGUNAKAN ALGORITMA GENETIKA DALAM MENYELESAIKAN PERMASALAHAN PENJADWALAN PROYEK KONSTRUKSI BANGUNAN - LUTFAN ANAS ZAHIR; KRISNA ACHMAD SUHUDI (JURNAL DAKTILITAS, 2023)
ABSTRACT The development of digitalization has accelerated since the covid-19 pandemic that hit the world in 2019.The role of digitalization in the economy is increasingly important, and is one of the enabling factors to increaseeconomic competitiveness in a country. Indonesia realizes the importance of digitalization for a country so that ithas initiated the mainstreaming of digital transformation and the implementation of the Strategic Priority Project(Major Project) "Information and Communication Technology Infrastructure to Drive Digital Transformation".The rapid development of technology provides many options for a construction service company to determine themethods and tools of Metaheruistic search algorithms that can be modeled or adapted to various problemsincluding scheduling. This scheduling system aims to minimize the average value of cost deviations. Critical pathmethod (CPM) is used to minimize cost deviation. Critical path analysis produces a length of time intended forcompletion of the project work duration. Determination of the critical path in this study using Genetic Algorithm.The results of the research on the data of 20 jobs with 3 constraint functions of duration, predecessor, and costobtained optimal critical path results with the critical path sequence ['D', 'A', 'B', 'G', 'C', 'E', 'H', 'F', 'K', 'I', 'L','J', 'M', 'N', 'O', 'P', 'Q', 'R', 'T', 'S']. Optimal Project Duration: 78 and Optimal Project Cost: 64000.Keywords: Critical Path Method (CPM), Genetic Algorithm, , Optimization, Scheduling,VScode. ABSTRAK Digitalisasi telah berkembang lebih cepat sejak pandemi COVID-19 melanda dunia pada 2019.Digitalisasi menjadi semakin penting dalam ekonomi dan merupakan salah satu komponen yang dapatmeningkatkan daya saing ekonomi suatu negara. Indonesia telah memulai pengarusutamaan transformasi digitaldan memulai Proyek Prioritas Strategis "Infrastruktur Teknologi Informasi dan Komunikasi untuk MendorongTransformasi Digital" sebagai bukti kesadaran negara akan pentingnya digitalisasi. Perkembangan teknologiyang semakin cepat memberikan banyak opsi bagi sebuah perusahaan jasa konstruksi untuk menentukan metodedan alat/ tools algoritma Metaheruistic pencarian yang dapat dimodelkan atau di adaptasikan pada berbagaipersamalahan termasuk pada penjadwalan. Sistem penjadawalan ini bertujuan untuk meminimalkan nilai rata –rata penyimpangan biaya. Metode jalur kritis atau Critical Path Method (CPM) digunakan untuk meminimalisirpenyimpangan biaya. Analisis lintasan kritis menentukan berapa lama waktu yang diperlukan untukmenyelesaikan proyek. Algoritma Genetika digunakan untuk menentukan garis besar penelitian ini. Hasilpenelitian pada data 20 pekerjaan dengan 3 fungsi kendala durasi, predesesor, dan cost memperoleh hasil criticalpath yang optimal dengan hasil urutan critical path ['D', 'A', 'B', 'G', 'C', 'E', 'H', 'F', 'K', 'I', 'L', 'J', 'M', 'N', 'O', 'P','Q', 'R', 'T', 'S']. Durasi optimal Project Duration: 78 dan Optimal Project Cost: 64000.Kata kunci: Algoritma Genetika, Critical Path Method (CPM), Optimasi, Penjadwalan, VScode.